Georeferenced and secure mobile health system for large scale data collection in primary care. (October 2016) - Sa, Joao H.G.; Rebelo, Marina S.; Brentani, Alexandra; Grisi, Sandra J.F.E.; Iwaya, Leonardo H.; Simplicio, Marcos A.; Carvalho, Tereza C.M.B.; Gutierrez, Marco A.
Highlights: We developed a secure mobile health system to collect information in primary care. We deployed the system at six primary care units involving more than of 28, 000 families or 96, 000 inhabitants. The proposed system has the potential to improve the efficiency of primary care data collection. The solution is cost-effective. Abstract: Introduction: Mobile health consists in applying mobile devices and communication capabilities for expanding the coverage and improving the effectiveness of health care programs. The technology is particularly promising for developing countries, in which health authorities can take advantage of the flourishing mobile market to provide adequate health care to underprivileged communities, especially primary care. In Brazil, the Primary Care Information System (SIAB) receives primary health care data from all regions of the country, creating a rich database for health-related action planning. Family Health Teams (FHTs) collect this data in periodic visits to families enrolled in governmental programs, following an acquisition procedure that involves filling in paper forms. This procedure compromises the quality of the data provided to health care authorities and slows down the decision-making process. Objectives: To develop a mobile system (GeoHealth) that should address and overcome the aforementioned problems and deploy the proposed solution in a wide underprivileged metropolitan area of a major city in Brazil. Methods: The proposed solution comprises three main components: (a) an Application Server, with a database containing family health conditions; and two clients, (b) a Web Browser running visualization tools for management tasks, and (c) a data-gathering device (smartphone) to register and to georeference the family health data. A data security framework was designed to ensure the security of data, which was stored locally and transmitted over public networks. Results: The system was successfully deployed at six primary care units in the city of Sao Paulo, where a total of 28, 324 families/96, 061 inhabitants are regularly followed up by government health policies. The health conditions observed from the population covered were: diabetes in 3.40%, hypertension (age >40) in 23.87% and tuberculosis in 0.06%. This estimated prevalence has enabled FHTs to set clinical appointments proactively, with the aim of confirming or detecting cases of non-communicable diseases more efficiently, based on real-time information. Conclusion: The proposed system has the potential to improve the efficiency of primary care data collection and analysis. In terms of direct costs, it can be considered a low-cost solution, with an estimated additional monthly cost of U$ 0.040 per inhabitant of the region covered, or approximately U$ 0.106 per person, considering only those currently enrolled in the system.